2021
DOI: 10.1007/s43452-021-00209-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of 3D printed cement mortar specimens using inkjet 3DP

Abstract: Investigations involving the experimental and numerical analysis of inkjet (powder-based) 3DP are relatively limited for cement mortar materials. This study, by using cement mortar specimens, aimed to determine the optimum strength of 3D printed structural members in all three planes by identifying the compressive strength of cubes, the modulus of elasticity and Poisson's ratio. In addition, this study aimed to analyse and verify the numerical model for 3D printed cementitious mortar (CP) prisms and beams usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The experimental testing did not reveal significant separation or debonding at the interfaces between the concrete, Sikadur mortar, and NSM components. Hence, the assumption of a successful bond was made in the FE modeling [40][41][42][43][44]. According to the findings of Banjara and Ramanjaneyulu [45], it was demonstrated that the utilization of the perfect bond yielded more accurate FE outcomes in comparison to the interface element, as evidenced by the experimental result comparison.…”
Section: Fe Model Set-upmentioning
confidence: 99%
“…The experimental testing did not reveal significant separation or debonding at the interfaces between the concrete, Sikadur mortar, and NSM components. Hence, the assumption of a successful bond was made in the FE modeling [40][41][42][43][44]. According to the findings of Banjara and Ramanjaneyulu [45], it was demonstrated that the utilization of the perfect bond yielded more accurate FE outcomes in comparison to the interface element, as evidenced by the experimental result comparison.…”
Section: Fe Model Set-upmentioning
confidence: 99%
“…In Selective Cement Activation (SCA), the particle bed consists of a dry mixture of cement and aggregates usually ranging in a volumetric ratio between 100/0 and 20/80 [1][2][3][4][5][6]. The fabrication of SCA components comprises the following steps: (1) depositing a layer of powder material in a confined region and p.r.n.…”
Section: Selective Cement Activationmentioning
confidence: 99%
“…As a result of the factors mentioned above, printing quality and pumping pressure considerably impact the quantity and arrangement of intra-and inter-filament voids, hence the behavior of printed structures. According to the literature, the compressive strength of 3D printed samples is directly influenced by the loading orientation due to anisotropy (Shakor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%